A cyclic frequency division non‐orthogonal multiple access system. (12th December 2021) - Sheela, N. Sathya; Stuwart, S. Lenty
Summary: In this paper, we have developed a downlink power domain non‐orthogonal multiple access (NOMA) system based on cyclic frequency division, where interleaved frequency division multiple access (IFDMA) is cyclically combined with NOMA. The newly developed cyclic frequency division NOMA (CFD‐NOMA) system has the benefit of both NOMA and IFDMA. The concept of superposed multiuser principle for non‐orthogonal resource allocation is used in each NOMA cluster, and the users' data associated with different clusters are separated based on IFDMA. Extreme channel conditions are considered among the users in each cluster. Based on channel gain, the users are differentiated as strong and cell edge users. At the strong user terminal, successive interference cancelation (SIC) is applied to decode the strong user data with the aid of the cell edge user data found from a hard decision, whereas the cell edge user terminal detects its signal only through the hard decision. The near‐far effect of the users present in a cluster, the amount of difference among their channel gain, and transmission power play an important role in detecting the cell edge and the strong users. The CFD‐NOMA system inherits an effective use of multipath channel, thereby reaps an increased cell edge user performance in terms of bit error rate (BER). Abstract : This paper presents a cyclic frequency division (CFD)‐based power domain non‐orthogonal multiple access (NOMA) system in which interleaved frequency division multiple access (IFDMA) is cyclically combined with NOMA. The superposed multiuser principle allows non‐orthogonal resource allocation in each NOMA cluster, whereas the IFDMA shares the user data among different clusters. The CFD‐NOMA system inherits an effective use of the multipath channel, thereby gains an increased cell edge user performance.